2017
DOI: 10.12717/dr.2017.21.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Egg Development and Larvae and Juveniles Morphology of Carp, Cyprinus carpio in Korean

Abstract: This study was conducted to observe egg and larvae morphological development of carp to obtain basic data for resource conservation and taxonomic research. Brood carp used in the research (total length 67.3-75.5 cm, average 71.0±3.45 cm) were bred in a circular rearing aquarium (600×300×100 cm) using a running water system from January to July, 2015. Breeding water temperature was maintained at 23.0-25.0℃(average 24.0℃). Fertilized carp eggs were translucent and globular, and their size was 1.75-1.89 mm (avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In the present experiment whole body surface of hatchlings was in direct contact of the contaminated water because it was devoid of scales. The scales develop 20 days post hatching 33,34 and protect the skin from predators, parasites and pollutants in the surrounding environment. This gets support from Escarrone et al 35 , who observed that accumulation of TCS in different tissues of Poecilia vivipara reached a steady state after one week of exposure in most of the tissues except for gill (having large surface area in direct contact with the pollutant) and gonad (having large lipid content).…”
Section: Discussionmentioning
confidence: 99%
“…In the present experiment whole body surface of hatchlings was in direct contact of the contaminated water because it was devoid of scales. The scales develop 20 days post hatching 33,34 and protect the skin from predators, parasites and pollutants in the surrounding environment. This gets support from Escarrone et al 35 , who observed that accumulation of TCS in different tissues of Poecilia vivipara reached a steady state after one week of exposure in most of the tissues except for gill (having large surface area in direct contact with the pollutant) and gonad (having large lipid content).…”
Section: Discussionmentioning
confidence: 99%
“…The first few hours after hatching, the larvae feed on their yolk and swim vertically to fill the swim bladder and become able to swim horizontally. The larval phase is a delicate and crucial stage of fish rearing (Park et al, 2017). During this phase, feeding plays an important role on the development of the larvae, including the development of the skeletal system.…”
Section: Discussionmentioning
confidence: 99%